PERANAN PUSAT KAJIAN PERLINDUNGAN ANAK (PKPA) DALAM PROSES PENDAMPINGAN KORBAN EKSPLOITASI SEKSUAL PADA ANAK DI KOTA MEDAN PROVINSI SUMATERA UTARA - Fitriani "; Tengku Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This thesis is submitted in order to quality holds a bachelor of sociology. With the title”The role of the center for study and child’s protection (PKPA) in the process of assisting victims of child sexual exploitation in city medan province north sumatera. Realities of everday life, criem of sexual esploitation of children is happening. Children are the group most vulnerable to. Child victim is often overlooked by various parties. Legal instruments in addressing the issue of sexual explotation is still minim. As children they also have the right to get the award and the best interests of her. For example, children have the right to be heard or been rewarded for her. For example, children have the right to be heard or been rewarded for his opinion it is intended thah the growth can be achieved to the maximum. Issues raised in this research is “ How the role of role of the center for study and child’s protection (PKPA) in the process of assisting victims of child sexual exploitation in city medan province north sumatera. This research aims to determine how the role of role of the center for study and child’s protection (PKPA) in the process of assisting victims of child sexual exploitation in city medan province north sumatera. Methods in this research using the case study method with qualitative approach. This research conducted center for study and child’s protection (PKPA) Province of north sumatera area surrounding child victims of sexual explotation. The data collection techniques with in depth interviwa and field observations. Then narrated the data obtained qualitatively using an inductive approach. Fact sheets on child victims of sexual explotation in disguise in research for the sake of the child protection. Data based on the data that has been collected and analyzed can be concluded the center for study and child’s protection (PKPA) in is effors to provide assistance to child victim have given the best thing for him climbers from center for study and child’s protection (PKPA) to assist and in accordance with the Standard Operating Procedures (SOP) that has been determind by the center for study and child’s protectionKeywords: Sexual Exploitation, child, Mentoring